Silymarin Targets β-Catenin Signaling in Blocking Migration/Invasion of Human Melanoma Cells - Vaid, Mudit (Public Library of Science, 2011)
Metastatic melanoma is a leading cause of death from skin diseases, and is often associated with activation of Wnt/β-catenin signaling pathway. We have examined the inhibitory effect of silymarin, a plant flavanoid from Silybum marianum, on cell migration of metastasis-specific human melanoma cell lines (A375 and Hs294t) and assessed whether Wnt/β-catenin signaling is the target of silymarin. Using an in vitro invasion assay, we found that treatment of human melanoma cell lines with silymarin resulted in concentration-dependent inhibition of cell migration, which was associated with accumulation of cytosolic β-catenin, while reducing the nuclear accumulation of β-catenin (i.e., β-catenin inactivation) and reducing the levels of matrix metalloproteinase (MMP) -2 and MMP-9 which are the down-stream targets of β-catenin. Silymarin enhanced: (i) the levels of casein kinase 1α, glycogen synthase kinase-3β and phosphorylated-β-catenin on critical residues Ser(45), Ser(33/37) and Thr(41), and (ii) the binding of β-transducin repeat-containing proteins (β-TrCP) with phospho forms of β-catenin in melanoma cells. These events play important roles in degradation or inactivation of β-catenin. To verify whether β-catenin is a potent molecular target of silymarin, the effect of silymarin was determined on β-catenin-activated (Mel 1241) and β-catenin-inactivated (Mel 1011) melanoma cells. Treatment of Mel 1241 cells with silymarin or FH535, an inhibitor of Wnt/β-catenin pathway, significantly inhibited cell migration of Mel 1241 cells, which was associated with the elevated levels of casein kinase 1α and glycogen synthase kinase-3β, and decreased accumulation of nuclear β-catenin and inhibition of MMP-2 and MMP-9 levels. However, this effect of silymarin and FH535 was not found in Mel 1011 melanoma cells. These results indicate for the first time that silymarin inhibits melanoma cell migration by targeting β-catenin signaling pathway.